2020
DOI: 10.1130/b35560.1
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting and reporting 40Ar/39Ar geochronologic data

Abstract: The 40Ar/39Ar dating method is among the most versatile of geochronometers, having the potential to date a broad variety of K-bearing materials spanning from the time of Earth’s formation into the historical realm. Measurements using modern noble-gas mass spectrometers are now producing 40Ar/39Ar dates with analytical uncertainties of ∼0.1%, thereby providing precise time constraints for a wide range of geologic and extraterrestrial processes. Analyses of increasingly smaller subsamples have revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(83 citation statements)
references
References 248 publications
(330 reference statements)
3
66
0
1
Order By: Relevance
“…A reliable plateau age is defined as experiments with at least 3 consecutive steps overlapping at 2-sigma, containing >50% of the 39 ArK, a Mean Square Weighted Deviate (MSWD) value<2.5, and with an 40 Ar/ 36 Ar inverse isochron intercept that does not deviate from atmospheric argon at 2-sigma. All the inverse isochron ages used the same steps as used in the weighted mean ages, and all relevant analytical data for the age calculations following standard practices (Schaen et al, 2020) can be found in in the supplementary material II.…”
Section: Ar/ 39 Ar Datingmentioning
confidence: 99%
“…A reliable plateau age is defined as experiments with at least 3 consecutive steps overlapping at 2-sigma, containing >50% of the 39 ArK, a Mean Square Weighted Deviate (MSWD) value<2.5, and with an 40 Ar/ 36 Ar inverse isochron intercept that does not deviate from atmospheric argon at 2-sigma. All the inverse isochron ages used the same steps as used in the weighted mean ages, and all relevant analytical data for the age calculations following standard practices (Schaen et al, 2020) can be found in in the supplementary material II.…”
Section: Ar/ 39 Ar Datingmentioning
confidence: 99%
“…To calculate these ages, high-temperature thermochronology is the most suitable approach (cf. Harrison, 1982;Zeitler, 1985;Reiners and Brandon, 2006;Schaen et al, 2020). To clarify, the closure temperatures of the systems will depend on the cooling rate of the rock and on kinetics, geometry, composition and size crystal (cf.…”
Section: High-temperature Thermochronology: Initial Cooling Agementioning
confidence: 99%
“…Furthermore, these thermochronometers have considerably higher closure temperatures than other thermochronometers suitable for calculating initial cooling ages (Harrison, 1982;Zeitler, 1985;Harrison et al, 2009;Reiners et al, 2017, pp. 231-253;Schaen et al, 2020) (Figure 3). In the biotite 40 Ar/ 39 Ar method, the thermometer is considered to be a low-temperature thermometer ( Figure 3) because the closure temperatures range from 330 to 280 °C (cf.…”
Section: High-temperature Thermochronology: Initial Cooling Agementioning
confidence: 99%
See 1 more Smart Citation
“…Blanks were monitored every 3 to 4 steps. All parameters and relative abundance values are provided in Table S4 following recommendations of Schaen et al (2020) and have been corrected for blank, mass discrimination and radioactive decay.…”
mentioning
confidence: 99%